The effect of human umbilical vein endothelial cells exosomes on the skin of intrinsic aging Wistar rats - Frieda Yanuar, Nugrohoaji Dharmawan, Indah Julianto, Arie Kusumawardani, Novan Adi Setyawan, Ervina Rosmarwati, Endra Yustin Ellistasari (Journal of Applied Pharmaceutical Science, 2023)
Aging is a complex process influenced by intrinsic and extrinsic factors. Intrinsic aging is affected by age, genetics, and hormones. A recent study has found that human umbilical vein endothelial cells (HUVEC) exosomes can serve as a new treatment for repairing and rejuvenating skin tissue. Therefore, this research aims to determine the effect of HUVEC exosomes on increasing type I collagen deposition on the skin of intrinsic aging Wistar rats. An experimental laboratory posttest-only control group study was conducted on 30 Wistar rats. The rats were divided into a control group (Group A) and treatment groups receiving 1% HUVEC exosome (Group B) and 1.5% HUVEC exosome (Group C). Collagen deposition was measured using Masson’s trichrome staining. Statistical analysis used the Kruskal–Wallis and Mann–Whitney tests (p-value < 0.05, significant). After 4 weeks, type I collagen deposition was significantly higher in the treatment groups than in the control group (p = 0.00). The mean values of collagen deposition (%) for Group A, Group B, and Group C were 15.87, 30.71, and 40.72, respectively. The Mann–Whitney test revealed that the HUVEC exosome had a significant effect on collagen deposition. Thereby, HUVEC exosomes can increase type I collagen deposition significantly and can be considered a therapeutic option for skin rejuvenation in future studies.